Second language task complexity : researching the cognition hypothesis of language learning and performance - Robinson, Peter (Task-based language teaching ;, 2011)
Understanding how task complexity affects second language learning, interaction and spoken and written performance is essential to informed decisions about task design and sequencing in TBLT programs. The chapters in this volume all examine evidence for claims of the Cognition Hypothesis that complex tasks should promote greater accuracy and complexity of speech and writing, as well as more interaction, and learning of information provided in the input to task performance, than simpler tasks. Implications are drawn concerning the basic pedagogic claim of the Cognition Hypothesis, that tasks sh.